Productive Culture and Urban Resilience: The Potential of Bamboo in Construction Technology by Eladio Dieste - Obata, Sasquia Hizuru; Fonseca, Nuno de Azevedo (Technical and Scientific Journal Green Cities, 2025)
ABSTRACT Objective – This study aims to investigate the potential of Bambusoideae (bamboo) as a sustainable and economically viable alternative to Lignum (wood) in architectural construction, with an emphasis on its application in formwork for structures based on Eladio Dieste's construction technology.Methodology – A mixed methodology was employed, integrating comparative analysis of the ecological footprints and economic viability of bamboo versus wood, in-depth study of Dieste's construction technology (focus on intensive use of labor, traditional knowledge and formal innovation), application of the concepts of “productive culture” (Deák) and “cosmic economy” (Dieste) as theoretical references, review of specialized literature, strategic economic analysis (including supply chains, training and treatments) and sustainability assessment (renewability, carbon sequestration, soil health). The approach culminates in a qualitative analysis that articulates technical and economic data with theoretical constructions to evaluate the promotion of urban resilience.Originality/Relevance – The originality lies in the articulation between Eladio Dieste's unique productive culture, characterized by the intensive use of skilled labor and a "cosmic economy" approach, and the introduction of bamboo as a strategic material to revisit this technology. The academic relevance is anchored in the pressing need to explore low-environmental-impact materials and construction models that promote sustainable urban resilience, filling a gap by connecting Dieste's technological legacy to contemporary socio-environmental demands, as opposed to purely financial models.Results – The results indicate that bamboo has significant environmental advantages, including a fast renewal cycle, high carbon sequestration capacity, and a positive contribution to soil health, in contrast to traditional logging. The technical feasibility of bamboo for complex geometric forms inspired by Dieste and its potential economic competitiveness through strategies such as the development of local supply chains, labor training, and protective treatments are demonstrated.Theoretical/Methodological Contributions – Theoretically, the study contributes by applying the concepts of "productive culture" and "cosmic economy" to the analysis of a contemporary material (bamboo), proposing a model of technological revisitation that values ​​the know-how and sustainability intrinsic to the process. Methodologically, it advances by integrating technical, economic, environmental and sociocultural analyses from the perspective of Dieste's technology, offering a replicable framework for evaluating alternative materials and construction processes.Social and Environmental Contributions – The social and environmental contributions include the promotion of construction practices with a lower ecological impact (reduction of soil degradation, CO2 sequestration) and the promotion of urban resilience through renewable materials. Additionally, it points to a development model that values ​​local skilled labor and regional economies, aligned with an "economy for sustainability" as opposed to a merely financial logic, promoting potentially more equitable and ecologically responsible urban development.
Keywords: Bamboo; Eladio Dieste; Urban resilience